Determinan Pengangguran Gender pada Negara Upper Middle Income di Negara APEC - Septia Priska Triana; Novya Zulva Riani (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to examine the factors influencing gender unemployment in upper-middle-income countries in APEC countries. The data used is panel data, namely data from 6 upper-middle-income countries in APEC countries from 2009-2023. The data used is secondary data obtained from the World Bank and UNDP. This research method is a quantitative method with a descriptive and associative research approach. This study uses panel data regression analysis with the best model selected being the Random Effect Model (REM). The results found that the number of productive-age population has a negative but insignificant effect on gender unemployment in upper-middle-income countries in APEC countries. The dependency ratio has a positive and significant effect on gender unemployment in upper-middle-income countries in APEC countries. Economic growth has a positive and significant effect on gender unemployment in upper-middle-income countries in APEC countries. Education has a negative but insignificant effect on gender unemployment in upper-middle-income countries in APEC countries